Aktivitas Analgesik dan Anti-Inflamasi Akar Eurycoma longifolia pada Mencit - Phebe Hendra; Wina Susana; Indriyani Permatasari; Jessy Florensia; Monita Natalia Siregar (JURNAL ILMU KEFARMASIAN INDONESIA, 2018)
This study was conducted to evaluate the analgesic and anti-inflammatory acitvities of Eurycoma longifolia root in mice. The analgesic effect was assessed using chemical stimuli (wrihting test) to induce peripheral pain in mice. The anti-inflammatory activity was determined using carrageenan-induced paw edema in mice. This study exhibites that Eurycoma longifolia root possesses analgesic and anti-inflammatory activities in mice.